Application of the C4.5 Algorithm for Early Cervical Cancer Classification - Taftazani Ghazi Pratama; Achmad Ridwan; Agung Prihandono (Urecol Journal. Part E: Engineering, 2021)
Cervical cancer is one of the cancers that is of global concern because of the high mortality rate in women. Preventive measures such as early detection are needed so that patients can get treatment more quickly. Fortunately, this disease can be prevented with the role of technology to help doctors in early detection of various types of cancer. The technology developed by the researchers is using machine learning algorithms. Therefore, in this study using the C4.5 algorithm to classify cervical cancer. This algorithm aims to classify 2 classes: people who have cervical cancer, people who are healthy. The results of the experiment obtained from the C4.5 algorithm are getting an accuracy of 98.61%, precision of 98.08%, and recall of 95.24% ROC curve shows 0.982%.